Association between physical functioning and food intake of patients with COPD - Grigoletto, Isis [UNESP] (2021)
Sao Paulo State Univ UNESP, Dept Physiotherapy, Postgrad Program Physiotherapy, Presidente Prudente, SP, Brazil